Policing U.K. Airports and Schedule 7 of the Terrorism Act 2000: The Young Passengers’ Perception of Security Measures - Wood, Steve (Terrorism and political violence, 2021)
Policing airports following 9/11 has been challenging with an emphasis on visibility and high levels of security checks for passengers. The focus has been on a form of ‘reassurance policing’ and an emphasis on procedural justice which is accepted as legitimate on the part of the public. However, there have been claims that that Muslim passengers are under greater suspicion than other passengers and have been subject to the practice of “racial profiling”. The powers under the Terrorism Act 2000, notably Schedule 7, have been under scrutiny as to the extent that they allow the police to stop and search suspects. This study reviews the opinions and experiences of young passengers at U.K. airports to see if they are reassured by policing and their opinions on profiling fellow passengers.